ANALISIS BEBAN KERJA DENGAN METODE WORKLOAD ANALYSIS (WLA) DALAM MENENTUKAN JUMLAH TENAGA KERJA YANG OPTIMAL PADA BAGIAN ASSEMBLING DI PT CAMBIUM FURNI INDUSTRI JEPARA (Science and Technology (SciTech), 2023)
The workforce at PT Cambium Furni Industri in the assembling section is considered lacking, so it often results in delays in the delivery of goods. From this problem it is necessary to conduct research to determine the number of workers in improving the quality of work of the employees they have. The purpose of this research is to determine the standard time and determine the optimal workforce requirements. The problems that occur are analyzed using the workload analysis method to provide the best solution. The results of this study are the workload borne by the employees of the assembly section of the new milano sofa and the new monaco sofa at PT. Cambium Furni Industri has an overload workload category that occurs in the assembly of the new Milano sofa seat assembly with a WLA value of 1.33 (overload). Whereas on the new Monaco sofa the leg assembly has a WLA value of 1.86 (overload), the seat assembly has a WLA value of 1.88 (overload). To overcome this problem, additional employees were added to reduce the overload workload on the assembly of the new milano sofa and the new monaco sofa, which originally had 1 employee added to 2 employees. After adding the number of employees, the WLA value which was originally overloaded became underloaded.